1972
DOI: 10.1037/h0082295
|View full text |Cite
|
Sign up to set email alerts
|

Number and position of visual stimuli as determinants of reaction time in schizophrenia.

Abstract: Reaction time in normal subjects has been shown to be linearly related to stimulus complexity, defined as the log of the number of equally probable stimuli to which a response may be made. Data (Scherer, 1970) were reanalyzed and compared with an earlier study of schizophrenic deficit by Venables (1958). Although experimental procedures were dissimilar, both studies found that increased complexity did not result in schizophrenics having steeper regression slopes than normal subjects. Consideration of the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Eysenck, Granger, and Brengelmann (1957), in a relatively uncontrolled perimetric study, reported significantly reduced peripheral vision among neurotic and psychotic as compared to normal subjects. Haley (1971) and Scherer (1972) found that chronic schizophrenics had longer reaction times to visual stimuli presented in the periphery than normal subjects. Neale (1971) found that schizophrenics were unable to recognize letters presented in the near periphery (2-3 degrees) than normals.…”
Section: Visual-spatial Extensitymentioning
confidence: 99%
“…Eysenck, Granger, and Brengelmann (1957), in a relatively uncontrolled perimetric study, reported significantly reduced peripheral vision among neurotic and psychotic as compared to normal subjects. Haley (1971) and Scherer (1972) found that chronic schizophrenics had longer reaction times to visual stimuli presented in the periphery than normal subjects. Neale (1971) found that schizophrenics were unable to recognize letters presented in the near periphery (2-3 degrees) than normals.…”
Section: Visual-spatial Extensitymentioning
confidence: 99%